2000
DOI: 10.1002/1520-6378(2001)26:1+<::aid-col41>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Color constancy in a rough world

Abstract: This article introduces a new psychophysical method for a performance-based view of color constancy, in which the task for the observer is to identify similar materials across illuminants despite possible appearance changes, and to simultaneously extract the relative colors of the illuminants. 15 The article also examines generality conditions for the task. Physical and neural constraints on chromatic signals make it possible to use simple affineheuristic algorithms to solve the correspondence problem for most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…(ii) Identifying surfaces across illuminants Zaidi (1998Zaidi ( , 2001) advocates a forced-choice measure of performance colour constancy in which the observer is required to identify like surfaces across illuminants, despite obvious differences in appearance. In a typical experiment, four surfaces are presented, two under each illuminant.…”
Section: Cone Sensitivities S(λ) M(λ) L(λ)mentioning
confidence: 99%
“…(ii) Identifying surfaces across illuminants Zaidi (1998Zaidi ( , 2001) advocates a forced-choice measure of performance colour constancy in which the observer is required to identify like surfaces across illuminants, despite obvious differences in appearance. In a typical experiment, four surfaces are presented, two under each illuminant.…”
Section: Cone Sensitivities S(λ) M(λ) L(λ)mentioning
confidence: 99%
“…The primate eye is fundamentally different from the shrimp, like a digital camera it possesses a single focusing apparatus for a dense array of photoreceptors. Using just three classes of broadly tuned cone photoreceptors, the primate visual system is able to distinguish the spectra of natural lights and objects sufficiently , while maintaining good spatial resolution, and providing the means to identify objects by their colors despite variations in ambient lights and surrounding scenes (Zaidi, 1998(Zaidi, , 2001. More classes of photoreceptors would improve the sampling of natural spectra (Nascimento, Foster, & Amano, 2005), but would seriously compromise spatial resolution.…”
Section: Evolution Of Neural Computations: Mantis Shrimp and Human Comentioning
confidence: 82%
“…I believe we have good reasons for thinking that, in certain conditions, perceptual systems can track and reidentify on the basis of perceptual state dispositions and perspectival features without ever representing object features. For example, with respect to color perception, Zaidi (1998Zaidi ( , 2001), Foster and Nascimento (1994), and Dannemiller (1993) have suggested that we might track objects perceived at different times not by comparing their object features, but by comparing their perceptual state dispositions in light of what we can estimate about the illumination. Crudely, the idea is that we can ask whether the two perceptual state dispositions lie in the graph of transformations that correspond to ecologically realistic changes in perspectival features (here, illumination).…”
Section: What Is Represented?mentioning
confidence: 90%
“…For one thing, subjects can, when asked, make matches of perspectival features, such as ambient illumination, as opposed to object features, such as surface lightness (Katz, 1935;Gilchrist, 1988;Hurlbert, 1989;Jameson and Hurvich, 1989;Zaidi, 1998). Indeed, subjects can even characterize the different incident illumination in the two regions of a scene -say, between a swath of forest in a scene illuminated by direct sunlight and the swath of forest in the same scene illuminated by partially could-obscured sunlight (Arend, 1993;Zaidi, 2001Zaidi, , 1998. These facts give us reasonably direct reasons for believing that subjects represent perspectival features at least some of the time.…”
mentioning
confidence: 96%